BIG BOOK MEDIA DEVELOPMENT OF REAL READING ABILITY AND COMMUNICATION ABILITY OF STUDENTS USING DIA TAMPAN STRATEGY: (Experimental Research at Class I SDIT Cendekia Purwakarta Purwakarta District, Purwakarta Regency) (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
This research was carried out on the basis of the low ability to read aloud students through the Big Book media as a learning medium based on the experience and knowledge of students. The purpose of this research is to improve the ability to read aloud and the ability to communicate through the big book media as a medium. This research was conducted using a dia tampan strategy learning. This study also uses research methods, namely Experimental Research on students of class I SDIT Cendekia Purwakarta, Purwakarta Regency. The indicator for the development of the big book media used is to improve the reading experience, errors and truths from large writings and illustrations, ideas for displaying books (book packaging display), as well as general ledger activities (in Umar). This Experimental Research was carried out 6 times. The results of this study indicate that the application of dia tampan strategy learning can improve the ability to read aloud and the communication skills of students with the big book media as a learning medium. In this study the creativity of students needs to be developed in particular the regional potential.